Ultrafast Nonlinear Fiber Optics: Single-Pulse Supercontinua and Specialty-Shape Pulses - Sukhoivanov, Igor A; Ramos Ortiz, Gabriel; Ibarra Manzano, Oscar; Andrade Lucio, Jose Amparo; Shulika, Oleksiy V (Photonics Letters of Poland, 2015)
Needs of science and technology for compact laser sources with specially shaped pulse waveforms or ultra-broad spectrum can be satisfied on the fiber-optic platform. Here we address transformation of ultrashort optical pulses in a variety of optical fibers aiming synthesis of specially shaped pulses and single-pulse flat-top supercontinuum. Results are discussed in the context of possible applications and experimental implementations. Full Text: PDF References J. M. Dudley, G. Genty, and S. Coen, "Supercontinuum generation in photonic crystal fiber", Rev. Mod. Phys. 78(4), 1135?1184 (2006). CrossRef A. M. Heidt, A. Hartung, G. W. Bosman, P. Krok, E. G. Rohwer, H. Schwoerer, and H. Bartelt, "Coherent octave spanning near-infrared and visible supercontinuum generation in all-normal dispersion photonic crystal fibers", Opt. Express, 19(4), pp. 3775?3787, (2011). CrossRef A. M. Heidt, J. Rothhardt, A. Hartung, H. Bartelt, E. G. Rohwer, J. Limpert, and A. Tünnermann, "High quality sub-two cycle pulses from compression of supercontinuum generated in all-normal dispersion photonic crystal fiber", Opt. Express 19, 13873-13879 (2011). CrossRef A. Hartung, A. M. Heidt, and H. Bartelt, "Design of all-normal dispersion microstructured optical fibers for pulse-preserving supercontinuum generation", Opt. Express 19, 7742-7749 (2011). CrossRef S. Boscolo and C. Finot, "Nonlinear Pulse Shaping in Fibres for Pulse Generation and Optical Processing", International Journal of Optics 2012, 159057 (2012) CrossRef J. M. Dudley, C. Finot, D. J. Richardson, G. Millot, "Self-similarity in ultrafast nonlinear optics", Nature Physics 3, pp. 597-603, (2007). CrossRef C. Finot, J.M. Dudley, B. Kibler, D.J. Richardson, G. Millot, "Optical Parabolic Pulse Generation and Applications", IEEE J. Quantum Electron. 45, pp. 1482-1489 (2009). CrossRef C. Finot, S. Pitois, and G. Millot, "Regenerative 40 Gbit/s wavelength converter based on similariton generation", Opt. Lett. 30, 1776?1778 (2005). CrossRef Parmigiani, P. Petropoulos, M. Ibsen, and D. J. Richardson, "Pulse retiming based on XPM using parabolic pulses formed in a fiber Bragg grating", IEEE Photon. Technol. Lett. 18, 829?831 (2006). CrossRef S. Boscolo, S. K. Turitsyn, and K. J. Blow, "Time domain all-optical signal processing at a RZ optical receiver", Opt. Express 13, 6217?6227 (2005). CrossRef T. T. Ng, F. Parmigiani, M. Ibsen, Z. Zhang, P. Petropoulos, and D. J. Richardson, "Compensation of Linear Distortions by Using XPM With Parabolic Pulses as a Time Lens", IEEE Photon. Technol. Lett. 20, 1097?1099 (2008). CrossRef S. O. Iakushev, O. V. Shulika, and I.A. Sukhoivanov, "Passive nonlinear reshaping towards parabolic pulses in the steady-state regime in optical fibers", Opt. Commun. 285, 4493?4499, (2012). CrossRef I. A. Sukhoivanov, S. O. Iakushev, O. V. Sulika, A. Díez, M. Andrés, "Femtosecond parabolic pulse shaping in normally dispersive optical fibers", Opt. Express, 21, pp. 17769-17785, (2013). CrossRef S. O. Iakushev, O. V. Shulika, I. A. Sukhoivanov, V. I. Fesenko, M. V. Andres, and H. Sayinc, "Formation of ultrashort triangular pulses in optical fibers", Opt. Express, 22(23), pp. 29119- 29134 CrossRef